When Economic Growth Is Not Enough: Determinants of Poverty in High-Poverty Regions of West Java Province - Murniati, Neni; Hutama, Sakti; Suryaman, Restu A; Ramdaniatulfitri, Intan (Universitas Gorontalo, 2026)
This study aims to analyze the determinants of poverty in five districts with high poverty levels in West Java Province. Indramayu Regency, Kuningan Regency, Tasikmalaya City, Majalengka Regency, and Cirebon Regency over the period 2009–2023. The explanatory variables include economic growth, Human Development Index (HDI), open unemployment rate, and income inequality. This study employs secondary data obtained from Statistics Indonesia (BPS) and applies panel data regression analysis. Model selection is conducted using the Chow test and Hausman test, indicating that the Fixed Effect Model is the most appropriate estimation approach. The empirical results reveal that all independent variables jointly have a significant effect on poverty levels. Partially, HDI, open unemployment rate, and income inequality are found to have a statistically significant effect on poverty, while economic growth does not show a significant impact. These findings suggest that poverty in regions with high poverty levels is multidimensional and cannot be explained solely by economic growth performance. Therefore, poverty reduction policies should emphasize improvements in human development, labor market conditions, and income distribution to achieve more inclusive and sustainable poverty alleviation.